2010
DOI: 10.1016/j.jom.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The integration of human resource and operation management practices and its link with performance: A longitudinal latent class study

Abstract: This paper reviews the literature on the association between lean production and performance. From this, propositions on the integration and evolution of operation and human resource management practices associated with the lean production concept are developed. Using 24 years of data on the use of seven core OM and HRM practices in British manufacturing firms, the potential link between integration in the use of practices and productivity is tested. In each year, three latent clusters are identified via order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 92 publications
2
80
0
15
Order By: Relevance
“…Similarly, we did not find substantial evidence that HR practitioners were generally included as partners in implementation or whether Lean Six Sigma is seen as part of a wider approach to managing change in terms of workplaces or organisational culture (Bonavia & Marin-Garcia, 2011;de Menezes et al, 2010;Torella et al, 2012).…”
Section: Hrm and Lean Managementmentioning
confidence: 67%
See 2 more Smart Citations
“…Similarly, we did not find substantial evidence that HR practitioners were generally included as partners in implementation or whether Lean Six Sigma is seen as part of a wider approach to managing change in terms of workplaces or organisational culture (Bonavia & Marin-Garcia, 2011;de Menezes et al, 2010;Torella et al, 2012).…”
Section: Hrm and Lean Managementmentioning
confidence: 67%
“…We have also been exploring the involvement of HRM practitioners in the PR processes. We infer from the literature that there is a link between PR and HRM, including the implications for training and skills development, job design and role restructuring, and consultation and involvement processes (Bonavia & Marin-Garcia, 2011;de Menezes, Wood, & Gelade, 2010;Torella et al, 2012). There is considerable literature on the industrial relations and labour-process aspects of Lean, for example exploring the question as to whether Lean is about empowering or controlling workers, whether Lean tends to be associated with a unitarist rather than a pluralist approach, hence undermining unions and collective organisation (Jones et al, 2013;Parker & Slaughter, 1995;Stewart et al, 2009), as well as the extent to which Lean seems to foster the engagement or exploitation of employees (Anderson-Connelly et al, 2002;Vidal, 2007).…”
Section: Hrm and Lean Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…When some of this research is explored closely it is clear that there are parallels with other areas of operations management. For example, a longitudinal study of LSS found a positive association between human resource management practices such as empowerment, extensive training and teamwork with TQM in the manufacturing and service sector (Lam et al, 2015;Stanton et al, 2014;Menezes et al, 2010). A further LSS study in the large "heavy automotive manufacturing supply" sector in developing countries (e.g.…”
mentioning
confidence: 99%
“…As pesquisas empíricas em GP&O têm reconhecido vários elementos do comportamento humano e demonstrado ganhos potenciais com a combinação de elementos das práticas de GRH e de GP&O (Kaynak, 2003;Ahmad & Schroeder, 2003;Jayaram, Droge & Vickery, 1999, 1999Huselid, 1995;Sila, 2007;Menezes, Wood & Gelade, 2010).…”
Section: Atual Intersecção Entre Operações E Recursos Humanosunclassified